ВОПРОСЫ ИЗУЧЕНИЯ КАРАКАЛПАКСКОЙ ЛИТЕРАТУРЫ В ИССЛЕДОВАНИЯХ ПЕРДЕБАЯ НУРЖАНОВА - Бекбергенова, М.Д. (SCIENCE and SOCIETY, 2024)
This article examines the literary works of the famous literary critic, Doctor of Philology, Professor P. Nurzhanov. The problems that the scientist reveals in his monographs «Contacting with People’s Memory», «Házirgi qaraqalpaq romanı poetikası» («Poetics of the modern Karakalpak novel»), as well as numerous literary articles concerning the development of Karakalpak literature, poetry, prose, and the creativity of individual authors are covered. , the problem of genre stylistic features of the Karakalpak novel, issues of literary relationships, creative individuality of writers, the study of the Karakalpak historical novel in the context of world literature.